Safety and tolerability of empagliflozin in East Asian patients with type 2 diabetes: Pooled analysis of phase I–III clinical trials - Yabe, Daisuke; Yasui, Atsutaka; Ji, Linong; Lee, Moon‐Kyu; Ma, Ronald Ching Wan; Chang, Tien‐Jyun; Okamura, Tomoo; Zeller, Cordula; Kaspers, Stefan; Lee, Jisoo; Kohler, Sven; Seino, Yutaka (Journal of diabetes investigation, 2019)
Aims/Introduction We investigated the safety and tolerability of empagliflozin (EMPA) in East Asian patients with type 2 diabetes. Materials and Methods Data were pooled from participants with type 2 diabetes evenly randomized to a placebo, EMPA 10 mg or EMPA 25 mg in 15 phase I–III trials. Adverse events (AEs) were analyzed in the subgroup of trial participants from East Asian countries/regions. Results In total, 709, 724 and 708 East Asian trial participants with type 2 diabetes received a placebo, EMPA 10 mg and EMPA 25 mg, respectively; total exposure was 953, 1,072, and 1,033 patient‐years in these groups, respectively. The EMPA and placebo groups had similar incidences of severe AEs, serious AEs and AEs leading to discontinuation. Incidences of hypoglycemia differed according to anti‐diabetes medication used at baseline. Higher rates of events consistent with genital infection were observed with EMPA (EMPA 1.5–1.7/100, placebo 0.2/100 patient‐years). Rates of AEs consistent with volume depletion were comparable among treatment groups (0.8–1.4/100 patient‐years), but in trial participants aged ≥65 years, the rate was greater with EMPA 25 mg (EMPA 25 mg 3.5/100, placebo 2.0/100 patient‐years). Incidences of events consistent with urinary tract infection, thromboembolic events, renal events, hepatic AEs, diabetic ketoacidosis, fractures and lower limb amputation were similar between EMPA and the placebo. Conclusions In the present pooled analysis, EMPA was well tolerated in East Asian type 2 diabetes patients based on >2,100 patient‐years’ exposure, consistent with results from the overall analysis population. In this pooled analysis of safety data from 15 Phase I–III trials, empagliflozin 10 and 25 mg were well tolerated in East Asian patients with type 2 diabetes based on >3,000 patient‐years’ exposure, consistent with results from the overall analysis population. The incidence of hypoglycemia differed according to glucose‐lowering medication used at baseline. Genital infections, but not UTIs, were more frequent in patients treated with empagliflozin than placebo.